Ali celovita sanacija vpliva na spremembo cen stanovanj? - Yau, Yung (Urbani izziv, 2011)
Urban decay is an inevitable outcome of the growth of most cities, including Hong Kong. Many old buildings in Hong Kong are dilapidated, and it is urgent to tackle urban decay in the city. Redeveloping dilapidated buildings has longbeen regarded as an effective solution to this urban problem. Yet, as suggested in the literature, redevelopment may be responsible for gentrifying neighbourhoods because it pushes up property and rental prices near redeveloped sites. However, there are still few empirical studies on how comprehensive redevelopment affects housing values in a neighbourhood. In this light, this study investigates the impacts of the Urban Renewal Authority's Argyle Street / Shanghai Street Redevelopment Project on the transaction prices of nearby housing. A set of panel data is employed and the change in the spatial price gradient before and after the redevelopment project is explored. The findings suggest that proximity to the project site had a significant positive impact on housing prices before the project. However, no change was seen in the spatial price gradient after completion of the project. These results confirm the findings of a previous study that housing prices do not respond to the change in the environmental quality resulting from comprehensive redevelopment.
Keywords: bivalno okolje; cene; HongKong; kvaliteta; mesta; sanacija; stanovanja